Tipologi Dam Karakteristik Komunikasi Organisasi Kemasyarakatan (Ormas) Islam Di Era Kekinian: Transfnrmasi, Otoritas, Dan Tantangan Digital - Noor Aziziah Bt. Adam; Ramsiah Tasruddin; Suf Kasman (CV. SINAR HOWUHOWU, 2026)
The digital era has transformed the communication landscape of Islamic mass organizations (ormas Islam) in Indonesia. This study aims to map the typologies and characteristics of contemporary Islamic organizations' communication in response to information technology disruption. Using a descriptive qualitative method based on library research, this article analyzes literature from books and national journals. The results indicate three main typologies of contemporary Islamic organization communication: (1) the Traditional-Transformative Typology, (2) the Modernist-Symbolic Typology, and (3) the Digital-Populist Typology. Present-day communication characteristics are marked by a shift in religious authority, the utilization of social media algorithms, a reliance on visual-interactive content, and efforts to engage Generations Z and Alpha through more inclusive or fragmented approaches. The implications of this research emphasize the importance of digital literacy adaptation for Islamic organizations to maintain public relevance and counter social polarization in the digital space.